Advancing Sustainable Development in PROPER-Registered Public Companies through Green Accounting and Material Flow Cost Accounting - Ananda, Rana Fathinah; Rahman, Fauziah; Rahmadhani, Sari Nuzullina; Tambunan, Sari Bulan; Tursina, Tursina (LP3M Universitas Putra Bangsa, 2025)
This study investigates the impact of Green Accounting and Material Flow Cost Accounting on Sustainable Development among publicly traded companies participating in PROPER during the 2019–2023 period. The research population encompasses 661 companies consistently listed throughout those years. Using a purposive sampling method, the study selected companies that published complete financial reports and were listed in PROPER for the entire observation period. Based on these criteria, a final sample of 9 companies was identified, resulting in 45 data observations across five years. Panel Data Regression was employed as the analytical technique. The findings reveal that both Green Accounting and Material Flow Cost Accounting exert a positive and significant partial influence on Sustainable Development. Furthermore, the combined effect of these two accounting approaches contributes meaningfully to the advancement of sustainability practices among companies listed on the Indonesia Stock Exchange during the observed period.